Using environmental DNA to monitor the reintroduction success of the Rhine sculpin (Cottus rhenanus) in a restored stream - Hempel, Christopher A; Peinert, Bianca; Beermann, Arne J; Elbrecht, Vasco; Macher, Jan-Niklas; Macher, Till-Hendrik; Jacobs, Gunnar; Leese, Florian (PeerJ Preprints, 2019)
As a consequence of the strong human impact on freshwater ecosystems, restoration measures are increasingly applied to restore and maintain their good ecological status. The ecological status of freshwaters can be inferred by assessing the presence of indicator species, such as the Rhine sculpin (Cottus rhenanus). However, traditional methods of monitoring fish, such as electrofishing, are often challenging and invasive. To augment or even replace the traditional fish monitoring approach, the analysis of environmental DNA (eDNA) has recently been proposed as an alternative, sensitive approach. The present study employed this modern approach to monitor the Rhine sculpin, a species that has been reintroduced into a recently restored stream within the Emscher catchment in Germany, in order to validate the success of the restorations. We monitored the dispersal of the Rhine sculpin using replicated 12S end-point PCR eDNA surveillance at a fine spatial and temporal scale to investigate the applicability of analyzing eDNA for freshwater ecosystem monitoring. We also performed traditional electrofishing in one instance to compare visual and eDNA-based assessments. We could track the dispersal of the Rhine sculpin and showed a higher dispersal potential of the species than we assumed. Furthermore, the eDNA analysis showed higher sensitivity for detecting the species than traditional electrofishing, although false negative results occurred at early reintroduction stages. Our results show that analyzing eDNA is capable of validating and tracking ecological reintroductions and contribute to the assessment and modelling of ecological status of streams.
Keywords: Biomonitoring; ecological restoration; eDNA; reintroduction; fish; rivers